Ginsenoside Rh2 augmented anti-PD-L1 immunotherapy by reinvigorating CD8+ T cells via increasing intratumoral CXCL10 - Mu-Yang Huang; Yu-Chi Chen; Wen-Yu Lyu; Xin-Yu He; Zi-Han Ye; Can-Yu Huang; Xin-Ling He; Xiuping Chen; Xiaobing Chen; Baoxian Zhang; Guoyin Kai; Xiaolei Zhang; et al. (Elsevier, 2023)
Profiting from the sustained clinical improvement and prolonged patient survival, immune checkpoint blockade of programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) axis has emerged as a revolutionary cancer therapy approach. However, the anti-PD-1/PD-L1 antibodies only achieve a clinical response rate of approximately 20%. Herein, we identified a novel combination strategy that Chinese medicine ginseng-derived ginsenoside Rh2 (Rh2) markedly improved the anti-cancer efficacy of anti-PD-L1 antibody in mice bearing MC38 tumor. Rh2 combined with anti-PD-L1 antibody (combo treatment) further triggered the infiltration, proliferation and activation of CD8+ T cells in the tumor microenvironment (TME). Depletion of CD8+ T cells by mouse CD8 blocking antibody abolished the anti-cancer effect of combo treatment totally. Mechanistically, combo treatment further increased the expression of CXCL10 through activating TBK1-IRF3 signaling pathway, explaining the increased infiltration of T cells. Employing anti- CXC chemokine receptor 3 (CXCR3) blocking antibody prevented the T cells infiltration and abolished the anti-cancer effect of combo treatment. Meanwhile, combo treatment increased the percentage of M1-like macrophages and raised the ratio of M1/M2 macrophages in TME. By comparing the anti-cancer effect of combo treatment among MC38, CT26 and 4T1 tumors, resident T cells were considered as a prerequisite for the effectiveness of combo treatment. These findings demonstrated that Rh2 potentiated the anti-cancer effect of PD-L1 blockade via promoting the T cells infiltration and activation, which shed a new light on the combination strategy to enhance anti-PD-L1 immunotherapy by using natural product Rh2.